Cone photoreceptor neuroprotection conferred by CNTF in a novel in vivo model of battlefield retinal laser injury. - Aslam, SA; Davies, W; Singh, MS; Charbel Issa, P; Barnard, A; Scott, R; Maclaren, R (2013)
PURPOSE: To develop a reproducible laboratory model to simulate a battlefield foveal laser injury and to test potential neuroprotective effects of a single injection treatment that might be administered in a military setting. METHODS: Frequency-doubled 532-nm Nd:YAG laser was used to induce a threshold retinal injury bilaterally in transgenic reporter mice that have fluorescent cones. Intravitreal injection of ciliary neurotrophic factor (CNTF) was then administered to the lasered eye and compared with a contralateral sham injection of saline. The effect on fluorescent cone cell survival was quantified using a confocal scanning laser ophthalmoscope (cSLO), TUNEL assays, and quantitative real-time PCR (qPCR). RESULTS: At 3 weeks post-laser, cSLO imaging showed that the proportion of surviving cones expressing green fluorescent protein (GFP) was greater in CNTF-treated (54.1 ± 5.15% of baseline count) than in sham-injected eyes (28.7 ± 4.4%), which was accompanied by a reduction in TUNEL-positive cells. This difference in cone survival persisted at the 6-week point (treated, 39.6 ± 3.2% versus sham, 18.0 ± 3.8%). These changes were accompanied by a reduction in TUNEL-positive cells. The Bcl-2/Bax ratio was increased in CNTF-treated eyes at 1 week postlaser exposure relative to controls. CONCLUSIONS: A single intravitreal injection of CNTF protein was shown to improve cone survival when administered immediately after laser exposure. Similar treatments with CNTF might also have a role in attenuating retinal laser damage sustained by combat personnel in the military setting.